Cars in Theatre, Theatre in Cars. A Case Study: Mobile Thriller (ENTHYMEMA, 2025)
This essay aims to provide insights into the relationship between theatre and the automobile through the lens of Mobility Studies and Performance Studies. While cars are commonly featured in visual media, they are rarely seen in theatre due to the inherent limitations of theatrical space. However, some artists have recently embraced this challenge, offering creative solutions both on stage and on the road in site-specific performances. Mobile Thriller, a monologue set in a car traveling on the Milan ring road, was initially performed in traditional theatre venues in Milan and Glasgow. It was later adapted for a performance inside a real car at the 2004 Edinburgh Fringe Festival. This essay discusses the differences between two versions of the play, highlighting how theatrical dramaturgy is always structured around the concept of space.
Keywords: Mobility Studies; Site-specific Performance; Edinburgh Fringe Festival; Theatre and Means of Transportation; Space and Dramaturgy